Large-Scale Electromagnetic Modeling for Multiple Inhomogeneous Domains (Communications in Computational Physics, 2018)
We develop a new formulation of the integral equation (IE) method forthree-dimensional (3D) electromagnetic (EM) field computation in large-scale modelswith multiple inhomogeneous domains. This problem arises in many practical applicationsincluding modeling the EM fields within the complex geoelectrical structuresin geophysical exploration. In geophysical applications, it is difficult to describe anearth structure using the horizontally layered background conductivity model, whichis required for the efficient implementation of the conventional IE approach. As a result,a large domain of interest with anomalous conductivity distribution needs to bediscretized, which complicates the computations. The new method allows us to considermultiple inhomogeneous domains, where the conductivity distribution is differentfrom that of the background, and to use independent discretizations for differentdomains. This reduces dramatically the computational resources required for large-scalemodeling. In addition, using this method, we can analyze the response of eachdomain separately without an inappropriate use of the superposition principle for theEM field calculations. The method was carefully tested for the modeling the marinecontrolled-source electromagnetic (MCSEM) fields for complex geoelectric structureswith multiple inhomogeneous domains, such as a seafloor with the rough bathymetry,salt domes, and reservoirs. We have also used this technique to investigate the returninduction effects from regional geoelectrical structures, e.g., seafloor bathymetry andsalt domes, which can distort the EM response from the geophysical exploration target.